Enhancing public integrity through governance, risk, and compliance implementation: A quantitative analysis from Indonesia - Fathia Fauziah Asshanti; Dominicus Savio Priyarsono; Linda Karlina Sari (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2025)
The decline in Indonesia’s national integrity index in recent years indicates a significant increase in corruption, particularly in public sector organizations. Although the government has implemented various policies and regulations to mitigate corruption, the results have yet to show substantial improvement. One potential approach to addressing this issue is the governance, risk, and compliance (GRC) framework, a strategy designed to strengthen accountability, transparency, and compliance. This research aims to analyze the impact of GRC implementation in public sector organizations in Indonesia, both nationally and regionally. While previous studies have explored the GRC for reducing corruption through theoretical or qualitative assessments, this research provides a quantitative analysis to measure the direct correlation between GRC and public sector integrity. The research methodology employed in this study includes a literature review, descriptive analysis, Pearson correlation test, and panel data regression. The results of this research indicate that the governance component is associated with a significant improvement in integrity across all public sectors. In contrast, the compliance component is related to improvements in local government. Several recommendations were formulated to improve the national integrity index, including strategies for enhancing GRC implementation.